Relationship of ICT and Company Success in Malaysian Companies - Yap, Robert Eng Onn (2004)
The importance of Information, Communications and Technology (ICT) as a key enabler to company performance is critical to ensure its survival in the global competitive environment. In order to measure relationship of ICT and company success, extensive literature reviews and a survey was carried out to gauge this relationship. The findings revealed information itself as the main success factor. Knowledgeable workers that are properly trained and developed also play a crucial part in this relationship. The findings also found no evidence of productivity paradox even though a number literature reviews have been written about it. Most probably it is due to difficulty in getting the right measurement to calculate productivity relating to ICT. Another success factor is the Internet is used as a new channel to market product or services.